Transforming Islamic Education Through Value-Based Leadership: A Narrative Review - Rahman, Gohar (Sinergi International Journal of Islamic Studies, 2025)
This narrative review explores the dynamics of Islamic educational leadership and its influence on institutional quality and transformation. The study aims to synthesize prevailing leadership models, evaluate their integration with Islamic values, and identify systemic enablers and constraints. Literature was gathered systematically from databases such as Scopus, Web of Science, ERIC, and Google Scholar using keywords including "Islamic educational leadership" and "transformational leadership in Muslim schools." Criteria for inclusion emphasized peer-reviewed sources focused on Islamic education contexts. Results indicate that transformational, spiritual, and charismatic leadership models dominate the Islamic education landscape. These models integrate core Islamic values such as tawhid, amanah, and qiwamah, contributing to effective governance, ethical decision-making, and stakeholder trust. The discussion reveals alignment with global leadership theories, affirming the universal relevance of value-based leadership. However, structural barriers such as gender biases, rigid organizational cultures, and inconsistent educational policies persist as significant impediments. Policy-driven solutions such as value-based leadership training, digital transformation strategies, inter-sectoral collaboration, and affirmative action for women leaders are recommended. These approaches foster inclusive, adaptive, and ethically grounded leadership. This review emphasizes the urgency of reforming Islamic educational leadership through integrated strategies that respond to contemporary challenges while preserving foundational religious principles.